A thermo-magnetohydrodynamic particle-fluid suspension moves peristaltically through a porous medium - N.M. Hafez; A.M. Abd-Alla; S.R. Mahmoud (Alexandria Engineering Journal)
A computational study is conducted on the magnetohydrodynamic peristaltic circulation of Casson nanofluid within a non-uniform conduit when Joule heating, thermal radiation, and combined mass/heat transportation impacts are present and the porous medium is saturated. The preparation of nanofluid involves the suspension of copper oxide nanoparticles in blood, with blood serving as the base fluid in this instance. Basic flow equations are linearized mathematically by assuming a high wavelength and a low Reynolds number. For both the fluid and particle phases, analytical formulae for temperature, velocity, concentration profiles, and volumetric flow rate are provided. Numerical integration is applied for estimating the friction force and the parameters of the pumping rate. The impact of the model’s different parameters is shown graphically in detail using the Mathematica program. The skin friction coefficient behavior as well as the Sherwood and Nusselt numbers behavior have been graphically illustrated for the relevant parameters. Notably, raising the medium permeability, Casson parameter, and Hartmann number improve temperature fields, velocity, Sherwood number, and skin friction coefficient; however, they have a reverse effect on concentration profiles and Nusselt number in the range −1<y<1. The fluid bolus shrinks in size and quantity in response to rising Hartmann numbers, Casson parameters, and medium permeability values. In addition to managing blood flow during surgery by adjusting magnetic field intensity, the current study has biomechanical implications for cancer therapy, medication administration, and chyme motility regulation in the gastrointestinal tract.